2013
DOI: 10.1155/2013/648420
|View full text |Cite
|
Sign up to set email alerts
|

PSCA and Oct-4 Expression in the Benign and Malignant Lesions of Gallbladder: Implication for Carcinogenesis, Progression, and Prognosis of Gallbladder Adenocarcinoma

Abstract: PSCA and Oct-4 have been thought as markers of cancer stem cells. Although overexpression of PSCA and Oct-4 in cancer has been reported, little is known about the clinical and pathological significance with PSCA and Oct-4 expression in gallbladder adenocarcinoma. In this study, overexpression of PSCA and Oct-4 was detected in gallbladder adenocarcinoma (54.6% and 55.6%). Less expression of PSCA and Oct-4 was detected in the pericancerous tissues (19.6% and 21.7%), gallbladder polyps (13.3% and 13.3%), and gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Prostate stem cell antigen (PSCA) is a glycosylphosphoinositolanchored cell surface antigen 20 that is overexpressed mainly in prostate cancer, 21 although its expression has also been reported in other tumors such as gallbladder adenocarcinoma 22 and gastric cancer. 23 Surprisingly, PSCA is frequently overexpressed in NSCLC, 20 although this requires confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate stem cell antigen (PSCA) is a glycosylphosphoinositolanchored cell surface antigen 20 that is overexpressed mainly in prostate cancer, 21 although its expression has also been reported in other tumors such as gallbladder adenocarcinoma 22 and gastric cancer. 23 Surprisingly, PSCA is frequently overexpressed in NSCLC, 20 although this requires confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that this protein is associated with the IFNα/β mediated immune response [ 11 ]. Subsequent reports showed that PSCA is likewise up-regulated in other cancer entities, such as gallbladder, urinary bladder cancer, renal cell carcinoma, pancreatic cancer or glioma [ 12 16 ], while it is down-regulated in others, such as esophageal and gastric cancers [ 17 20 ]. The clinical utility of PSCA as a diagnostic marker or therapeutic target has been demonstrated in prostrate, pancreatic and bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate stem cell antigen (PSCA) is a member of Ly-6/Thy-1 family of glycosylphosphatidyl-inositol (GPI)-anchored cell-surface proteins having a crucial role in cell adhesion, proliferation, and survival [ 14 ]. PSCA was found to be aberrantly expressed in several human cancers, and since it has restricted expression in normal tissues, PSCA represents an ideal target for cancer diagnosis and therapy [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Human PSCA gene maps on chromosome 8q24.2 containing 464 SNPs.…”
Section: Introductionmentioning
confidence: 99%